Timing of oomycete-specific fungicide application impacts the efficacy against fruit rot disease in arecanut - Balanagouda, Patil; Shil, Sandip; Sridhara, Shankarappa; Pandian, R. Thava Prakasa; Thube, Shivaji Hausrao; Hegde, Vinayaka; Sayed, Shaban R. M.; Casini, Rayan; Narayanaswamy, Hanumappa (Frontiers in Plant Science, 2023)
Fungicidal application has been the common and prime option to combat fruit rot disease (FRD) of arecanut (Areca catechu L.) under field conditions. However, the existence of virulent pathotypes, rapid spreading ability, and improper time of fungicide application has become a serious challenge. In the present investigation, we assessed the efficacy of oomycete-specific fungicides under two approaches; i) three fixed timings of fungicidal applications i.e., pre, mid, and post-monsoon period (EXPT1), and ii) pre-defined different fruit stages i.e., button, marble, and pre-mature stages (EXPT2).Fungicidal efficacy in managing FRD was determined from evaluations of FRD severity, FRD incidence, and cumulative fallen nut rate (CFNR) by employing generalized linear mixed models (GLMMs). In EXPT1, all the tested fungicides reduced FRD disease levels by >65% when applied at pre-or mid-monsoon compared to untreated control, with statistical differences among fungicides and timings of application relative to infection. In EXPT2, the efficacy of fungicides was comparatively reduced when applied at pre-defined fruit/nut stages, with statistically non-significant differences among tested fungicides and fruit stages. A comprehensive analysis of both experiments recommends that the fungicidal application can be performed before the onset of monsoon for an effective management of arecanut FRD. In conclusion, the timing of fungicidal application based on the monsoon period provides better control of FRD of arecanut than an application based on the developmental stages of fruit under field conditions.